Osteoblast studied on gelatin based biomaterials in rabbit Bone Bioengineering - Yadav N.; Srivastava P. (My University, 2025)
The bone-derived-osteoblast seeded biomaterials scaffold in tissue engineering, have displayed prominence in the treatment of the osseous medical condition. In vitro osteogenesis of rabbit osteoblast cell (rOb) from bone tissue (rT) and MSC-derived rOb from bone marrow (rM) on Gelatin-Hydroxyapatite (HG) based biomaterials was investigated. In this work, lyophilized biomaterial was prepared by the addition of amorphous chitosan (‘C’) to ‘H’ dispersed in ‘G’ matrix, to find its role in biomaterials biocompatibility. Isolated rOb seeded biomaterials were studied using CLSM and flow cytometry for proliferation potential. The biomaterial's core and surface morphology was studied from SEM-EDX and AFM respectively. Upon co-culture with HCG, rT over rM showed rabbit bone extracellular matrix (ECM) mimicking properties both in in vitro studies and biomaterials micro architecture. The in vitro metabolic behaviour was studied by Alamar Blue (AB) assay, DNA content using Hoechst 33258, potency via the activity of Alkaline Phosphatase (ALP), Calcium's relative content by Alizarin Red S (ARS) assay. A novel combination of biomaterials-cell interaction was observed when rT was co-cultured with HCG and proved effective in osteogenesis with regard to Bone Bioengineering. © 2019 Elsevier B.V.